Work Pattern and Quality of Life Among Construction Workers in Kuniamuthur Village in Coimbatore District - E., Tesla (Journal of Social Work Education and Practice, 2023)
The Indian construction industry is a major part of the economy and conduit for a substantial part of its development investment and poised for growth on account of industrialization, urbanization, economic development and people’s rising expectations for improved quality of living. Quality of life of the employees in the construction sector is an important factor towards the growth of the industry. The researcher had adopted descriptive research design for the study. In the Kuniamuthur village, the researcher had collected 100 samples from the construction sector by using purposive sampling method. Among the total respondents, nearly half of the respondents have a moderate level of quality of life in their work. Governments and private building contractors should take initiatives to improve the quality of life of the workers and also should focus on improving policies on welfare measures of the construction workers